1988
DOI: 10.1111/j.1532-5415.1988.tb01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Alzheimer Patients Healthier?

Abstract: At an active outpatient geriatric program the gerontological team observed that Alzheimer patients appear to have fewer physical ailments than other elderly patients. To test this hypothesis, we reviewed a sample of 348 clinic patients. One hundred forty-three had a normal mental status; 75 had Alzheimer's disease as defined by DSM-III criteria; 139 had an abnormal mental status attributed to other etiologies. The number of diagnoses was compiled in each of the three groups. The average number of diagnoses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
89
6
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 10 publications
12
89
6
4
Order By: Relevance
“…In addition it supports the personal experience of the authors reported elsewhere [21]. This finding is somewhat surprising considering DAT sufferers may be healthier than other age controlled elderly [31] and by definition only suffer initially from a loss in cognitive domains [12]. A possible explanation is that moderate DAT patients who showed shorter step length, lower gait speed, lower stepping frequency, greater step-to-step variability, and greater sway path [32].…”
Section: Discussionsupporting
confidence: 71%
“…In addition it supports the personal experience of the authors reported elsewhere [21]. This finding is somewhat surprising considering DAT sufferers may be healthier than other age controlled elderly [31] and by definition only suffer initially from a loss in cognitive domains [12]. A possible explanation is that moderate DAT patients who showed shorter step length, lower gait speed, lower stepping frequency, greater step-to-step variability, and greater sway path [32].…”
Section: Discussionsupporting
confidence: 71%
“…Some studies suggest that the prevalence of Alzheimer disease is increased in type 2 diabetes (58 -60), whereas in others, it has been reported as decreased (61)(62)(63)(64)(65)(66) or comparable (48,49,(67)(68)(69)(70)(71). A confounding factor in these studies (including the current one) is that Alzheimer disease is often accompanied by a decreased BMI presumed to be a result of decreased food intake.…”
Section: Discussionmentioning
confidence: 44%
“…One reason for our findings could be related to the types of dementias and the comorbidities associated with them. As an example, patients with vascular dementia had the highest comorbidity scores, related to conditions associated with cardiovascular risk: hypertension, hyperlipidemia, stroke, peripheral vascular disease and others [36][37][38][39] Table 5: Unadjusted and adjusted cox proportional hazard ratios for in-hospital Dementia mortality by nis year and age group: african americans, hispanics vs. whites*.…”
Section: Discussionmentioning
confidence: 99%